Mitochondrial‐targeted peptide rapidly improves mitochondrial energetics and skeletal muscle performance in aged mice. Issue 5 (11th June 2013) - Siegel, Michael P.; Kruse, Shane E.; Percival, Justin M.; Goh, Jorming; White, Collin C.; Hopkins, Heather C.; Kavanagh, Terrance J.; Szeto, Hazel H.; Rabinovitch, Peter S.; Marcinek, David J.
Summary Mitochondrial dysfunction plays a key pathogenic role in aging skeletal muscle resulting in significant healthcare costs in the developed world. However, there is no pharmacologic treatment to rapidly reverse mitochondrial deficits in the elderly. Here, we demonstrate that a single treatment with the mitochondrial‐targeted peptide SS‐31 restores in vivo mitochondrial energetics to young levels in aged mice after only one hour. Young (5 month old) and old (27 month old) mice were injected intraperitoneally with either saline or 3 mg kg−1 of SS‐31. Skeletal muscle mitochondrial energetics were measured in vivo one hour after injection using a unique combination of optical and 31P magnetic resonance spectroscopy. Age‐related declines in resting and maximal mitochondrial ATP production, coupling of oxidative phosphorylation (P/O), and cell energy state (PCr/ATP) were rapidly reversed after SS‐31 treatment, while SS‐31 had no observable effect on young muscle. These effects of SS‐31 on mitochondrial energetics in aged muscle were also associated with a more reduced glutathione redox status and lower mitochondrial H2O2 emission. Skeletal muscle of aged mice was more fatigue resistant in situ one hour after SS‐31 treatment, and eight days of SS‐31 treatment led to increased whole‐animal endurance capacity. These data demonstrate that SS‐31 represents a new strategy for reversing age‐related deficits in skeletal muscle with potential for translation into human use.